A preliminary study on the relationship between parasitaemia and cytokine expression of peripheral blood cells in trypanosoma vivax‐experimentally infected cattle - Junior, Otavio Luiz Fidelis [UNESP]; Sampaio, Paulo Henrique [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; Wijffels, Gene; Cadioli, Fabiano Antonio [UNESP] (MDPI, 2021)
Trypanosoma vivax outbreaks have been reported with increasing frequency worldwide, causing significant economic losses in livestock. Though several studies have suggested that cytokine responses may influence infection caused by Trypanosoma sp., their exact role remains unclear and may vary according to the animal species and parasite strain. The present study aimed to evaluate cytokine expression of peripheral blood cells from three Girolando dairy cows experimentally infected with T. vivax. For this purpose, blood samples were collected prior to the inoculation on the day of inoculation (D0), the day after inoculation (D1), and then every seven days up to 119 days after infection (DAI). Each animal presented a unique pattern of cytokine expression. While a tendency of a Th1 cytokine response was observed during the patent phase (presence of circulating parasites), an increase of Th2 cytokine expression was found at the beginning of the subpatent phase (low parasitaemia or aparasitaemic periods). In animals that presented a better control of parasitaemia, IL‐6 and IFNγ increased during most of the trial period. On the other hand, the cow that presented reduction of IL‐1β, IL‐2, and TNFα during the entire period did not control parasitaemia properly. A balance between the Th1 and Th2 profile is beneficial for parasite control and animal health. The results found in the present study are a first step towards elucidating the dynamics of cattle’s inflammatory response against T. vivax, requiring future studies focusing on the role of key cytokines on the controlling of parasitaemia in different stages of bovine trypanosomosis.
Keywords: Host–parasite relationship; RT‐qPCR; Th1; Th2; Trypanosomosis